2005
DOI: 10.1007/s00425-005-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6P dehydrogenase in Chlorella sorokiniana (211/8k): an enzyme with unusual characteristics

Abstract: In Chlorella sorokiniana (211/8k), glucose-6 phosphate dehydrogenase (G6PDH-EC 1.1.1.49) activity is similar in both N-starved cells and nitrate-grown algae when expressed on a PCV basis. A single G6PDH isoform was purified from Chlorella cells grown under different nutrient conditions; the presence of a single G6PDH was confirmed by native gels stained for enzyme activity and by Western blots. The algal G6PDH is recognised only by antibodies raised against higher plants plastidic protein, but not by chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…This result may be due to the lower concentration of interfering compounds (e.g., proteins) present in microalgae grown under nitrogen starvation conditions. It has been reported (Esposito et al 2006) that the protein content in green microalgae is about threefold higher in nitrogensufficient cells with respect to nitrogen-starved cells. According to Chow and Landhäusser (2004), watersoluble compounds such as proteins react with the concentrated sulfuric acid in the glucose assay and, therefore, significantly interfere with the absorbance reading.…”
Section: Resultsmentioning
confidence: 99%
“…This result may be due to the lower concentration of interfering compounds (e.g., proteins) present in microalgae grown under nitrogen starvation conditions. It has been reported (Esposito et al 2006) that the protein content in green microalgae is about threefold higher in nitrogensufficient cells with respect to nitrogen-starved cells. According to Chow and Landhäusser (2004), watersoluble compounds such as proteins react with the concentrated sulfuric acid in the glucose assay and, therefore, significantly interfere with the absorbance reading.…”
Section: Resultsmentioning
confidence: 99%
“…Esposito et al. have shown that in nitrate fed barley seedlings, GOGAT activity was at the maximum after 3 days, whereas in ammonium supplied plants, the highest rates of GOGAT activity were observed after 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…The NADH-GOGAT (EC. 1.4.1.14) and Fd-GOGAT (EC 1.4.7.1) activities were detected, as described by Esposito et al [52].…”
Section: Enzymatic Activities Assaymentioning
confidence: 55%